Compiler construction using Java, JavaCC, and Yacc - Dos Reis, Anthony J. (Wiley-IEEE Computer Society, 2012)
"Compiler Construction Using Java, JavaCC, and Yacc by Anthony J. Dos Reis covers every topic essential to learning compilers from the ground up and is accompanied by a powerful and flexible software package for evaluating projects as well as several tutorials, well-defined projects, and test cases"-- Provided by publisher